Realizing Pancasila Student Profiles in the School Environment through the Internalization of Character Education - Reviandari Widyatiningtyas; Elly Retnaningrum; Sugisman; Syafa'at Ariful Huda; Alek Andika (Widya Accarya, 2023)
Pancasila, which is the basis of the state and the nation's ideology, seems to be fading. This is marked by the attitudes and actions of Indonesian students who are no longer oriented and reflect Pancasila values. This research aims to determine the internalization of character education in an effort to realize the Pancasila Student Profile. This research belongs to the type of descriptive qualitative research. Data collection techniques used literature studies and documentation. The data obtained were then analyzed and described qualitatively. This research showed that the efforts made by schools to realize the Pancasila Student Profile in the school environment through educational integration (1) Faith, piety to God Almighty and noble character, are carried out by inviting children to always pray before starting and ending learning activities; (2) Global diversity is carried out by teaching students not to choose friends on the basis of ethnicity, religion, race and between groups; (3) Mutual cooperation is realized in the form of group learning and cleaning activities carried out by students in the school environment; (4) Independent is done by giving students tasks that must be done independently; (5) Critical reasoning is done by the teacher by presenting information on social media that is viral and confusing to be discussed in class; (6) Creativity can be realized by teachers by providing space and freedom to work